2022
DOI: 10.3389/fcimb.2022.816386
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Small Molecules to the Control of Typical Species Associated With Oral Infectious Diseases

Abstract: Oral microbial dysbiosis is the major causative factor for common oral infectious diseases including dental caries and periodontal diseases. Interventions that can lessen the microbial virulence and reconstitute microbial ecology have drawn increasing attention in the development of novel therapeutics for oral diseases. Antimicrobial small molecules are a series of natural or synthetic bioactive compounds that have shown inhibitory effect on oral microbiota associated with oral infectious diseases. Novel small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 167 publications
0
2
0
Order By: Relevance
“…In the oral cavity, wound healing is not just limited to recovering from injury or surgery, but it also covers the biological processes that occur after diseases including cancer and infections [ 2 ]. Various strategies have been employed to promote oral tissue repair [ 34 ]. However, the adopted strategies, including non-surgical or surgical modalities combined with antimicrobial therapies, have not always achieved the wished success.…”
Section: Discussionmentioning
confidence: 99%
“…In the oral cavity, wound healing is not just limited to recovering from injury or surgery, but it also covers the biological processes that occur after diseases including cancer and infections [ 2 ]. Various strategies have been employed to promote oral tissue repair [ 34 ]. However, the adopted strategies, including non-surgical or surgical modalities combined with antimicrobial therapies, have not always achieved the wished success.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that caffeic acid can inhibit the growth of oral pathogens, such as Streptococcus mutans and Porphyromonas gingivalis, which are associated with dental caries and periodontitis, respectively. Caffeic acid works by disrupting the bacterial cell membrane and inhibiting the activity of enzymes involved in bacterial metabolism [34].…”
Section: Discussionmentioning
confidence: 99%
“…Dental biofilm is composed of a wide variety of microorganisms; microbial dysbiosis in this biofilm contributes to the occurrence of both caries and periodontal diseases [ 9 , 10 ]. Based on epidemiological and experimental studies, oral health care providers recommend that effective oral hygiene, through the mechanical removal of the biofilm, be conducted to maintain optimal oral health [ 11 ].…”
Section: Introductionmentioning
confidence: 99%